2014
DOI: 10.1016/j.buildenv.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of a building's thermal properties on pupils' thermal comfort in junior school classrooms as determined in field studies

Abstract: Recent thermal comfort research in a light-weight junior school building showed that children were more sensitive to higher temperatures than adults and subsequently that current thermal comfort standards were not appropriate for the assessment of their thermal environment. This paper presents a comparison of these survey results to those from a survey conducted in a medium-weight school building, in order to evaluate the role of the construction type on the results. Both surveys followed the same methodology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 26 publications
1
27
0
5
Order By: Relevance
“…shown by the sketches in Teli et al, 2014). This means that the lightweight building has a quicker response to outdoor temperature changes compared to the Victorian building.…”
Section: Case Study Schoolsmentioning
confidence: 97%
“…shown by the sketches in Teli et al, 2014). This means that the lightweight building has a quicker response to outdoor temperature changes compared to the Victorian building.…”
Section: Case Study Schoolsmentioning
confidence: 97%
“…In another study, Teli et al [193] show the adjustments that should be made in the current comfort criteria to evaluate the thermal perception of children in various climates. The current thermal comfort criteria lead to an underestimation of the thermal sensation of children during the summer [194]. The study of De Giuli et al [195] held in a school in Padova (Italy), found no match between the PMV/PPD and the children's' ASV neither between the adaptive model nor the ASV [196].…”
Section: Thermal Comfort In Schoolsmentioning
confidence: 99%
“…Thus, children's thermal comfort may be shown to be different from that of adults because their biological characteristics differ from those of adults and the characteristics of their activity spaces such as the numbers of occupants in school classrooms (kindergarten, elementary/middle/high school) are diverse [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because standards for children's thermal comfort have not been set, several studies such as those conducted by Yun et al, and Teli D et al, used adult PMV models to compare children's thermal comfort with adults' thermal comfort [15,16]. According to the results, children's thermal comfort showed different characteristics from those of adults' thermal comfort and because major factors of PMV models, such as metabolic rates, skin temperatures, and thermal sensation, were different from those of children's thermal comfort, there are limitations in applying the PMV models to children's thermal comfort [8].…”
Section: Introductionmentioning
confidence: 99%